Silk from Indian paper wasp: Structure prediction and secondary conformational analysis. (3rd November 2020) - Chawla, Shikha; Seit, Sinchan; Murab, Sumit; Ghosh, Sourabh
Abstract: The pupae of Indian paper wasp, Ropalidia marginata, produce silk that covers the opening of each cells in their hives, which probably helps in thermoregulation and providing mechanical stability. In this study an attempt has been made to investigate the amino acid composition and protein structure of Indian wasp silk using bioinformatics and experimental tools. The amino acid analysis of the regenerated solubilized wasp silk revealed high alanine and serine content that increases the propensity of α-helical and random coil and/or β-sheet structure respectively. The Matrix Assisted Laser Desorption/Ionization-Time Of Flight/Time Of Flight based protein fingerprinting analysis of the regenerated solubilized wasp silk revealed its short-range sequences. The protein modeling studies indicated the presence of predominant coiled coil α-helical and random coil structure in the protein isolated from wasp hive caps, similar to previous reports from the Vespoidea family. Fourier transform infrared spectroscopic analysis and X-ray diffraction analysis of the native paper wasp cap revealed the presence of mix of coiled coil α-helix and β-sheet structure in outer regions; whereas inner region contains tannin/intermolecularly bonded hydroxyl groups of polyphenols. The present study is first report to generate valuable insights about the chemical composition and secondary structure prediction of Indian paper wasp silk and highlight on nature's novel modus operandi to engineer unique functional fibrous matrix. Graphical abstract: Image 1 Highlights: First report on silk produced by pupae of Indian paper wasp. High alanine and serine corresponding to coiled coil α-helix and β-sheets. Tannin and Transglutaminase induced crosslinking makes wasp silk insoluble in chaotropic agent.